1997
DOI: 10.1145/263932.264023
|View full text |Cite
|
Sign up to set email alerts
|

The macroscopic behavior of the TCP congestion avoidance algorithm

Abstract: In this paper, we analyze a performance model for the TCP Congestion Avoidance algorithm. The model predicts the bandwidth of a sustained TCP connection subjected to light to moderate packet losses, such as loss caused by network congestion. It assumes that TCP avoids retransmission timeouts and always has sucient receiver window and sender data. The model predicts the Congestion Avoidance performance of nearly all TCP implementations under restricted conditions and of TCP with Selective A c knowledgements ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
712
1
16

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,177 publications
(738 citation statements)
references
References 10 publications
9
712
1
16
Order By: Relevance
“…Most of these make the simplifying assumption that every packet gets dropped with probability p independent of all other packet drops. Under this assumption, several papers [20,18] show that for low values of p, TCP throughput is proportional to 1/ √ p. The same result was proved in [24] for more elaborate models of TCP. [25] showed that throughput decreases faster (roughly proportional to 1/p) at higher values of p. All these papers assume constant round-trip times.…”
Section: Probabilistic Analysis Of Tcp Congestion Controlsupporting
confidence: 58%
“…Most of these make the simplifying assumption that every packet gets dropped with probability p independent of all other packet drops. Under this assumption, several papers [20,18] show that for low values of p, TCP throughput is proportional to 1/ √ p. The same result was proved in [24] for more elaborate models of TCP. [25] showed that throughput decreases faster (roughly proportional to 1/p) at higher values of p. All these papers assume constant round-trip times.…”
Section: Probabilistic Analysis Of Tcp Congestion Controlsupporting
confidence: 58%
“…This behavior is completely different from the one observed for TCP flows that are always on, for which it has been shown that the steady-state average sending rate is approximately given by c RT T √ p drop , where RT T denotes the average round-trip time, p drop the per-packet drop rate, and c a constant ranging from 1.225 to 1.310 depending on the method used to derive the equation [8,20,35,36,40]. This equation is valid at least for simple network topologies, small values of p drop , and one acknowledgments per ACK packet (n ack = 1).…”
Section: Reduced-order Modelmentioning
confidence: 92%
“…A great deal of effort has been placed in characterizing the steady-state behavior of these flows [35,36,40,41,46]. In particular, in studying the relationship between the average transmission rate µ, the average round-trip time RT T , and the per-packet drop rate p drop for a single TCP flow.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, if many packets arrive within a short period of time, the buffer may eventually overflow, so that an increase in the network load results in a decrease of useful work done due to: undelivered packets, packets consuming resources that are dropped later in the network, spurious retransmissions of packets still "in flight" (leading to even more load)… In the mid-1980s, the Internet converged to a halt until Jacobson/Karels devised TCP congestion control [3], so that the general approaches to avoiding drops of many packets and the so-called congestion collapse include: pre-arranging bandwidth allocations (with drawbacks of requiring negotiation before sending packets and potentially low utilization, differential pricing, i.e. not dropping packets for the highest bidders, and dynamic adjustment with testing the level of congestion with speeding up when there is no congestion and slowing down otherwise (where drawbacks are: suboptimality, complex implementation) [4].…”
Section: Flow Control and Managing Congestion In Tcp/ip Networkmentioning
confidence: 99%
“…Therefore, upon success with the last window of data, the TCP sender load should increase linearly, and decrease multiplicatively, upon packet loss [4]. This becomes a necessary condition for the stability of TCP [5], [6], [7].…”
Section: Flow Control and Managing Congestion In Tcp/ip Networkmentioning
confidence: 99%